Teamwork attitudes, interest and self-efficacy between online and face-to-face information technology students. Issue 5 (12th August 2019) - Konak, Abdullah; Kulturel-Konak, Sadan; Cheung, Gordon W.
Abstract : Purpose: Challenges of teamwork in online classes may adversely affect students' future attitudes toward teamwork. Further, there is a concern about whether online programs foster students' teamwork skills. To answer these questions, the purpose of this paper is to compare online and face-to-face students' attitudes toward teamwork, interest in learning teamwork skills and teamwork self-efficacy. Design/methodology/approach: The authors developed a conceptual model explaining how students' background, engagement in learning teamwork, teamwork self-efficacy and interest in learning teamwork affect attitudes toward teamwork and rigorously tested the model for a meaningful comparison between online and face-to-face students. Attitudes toward teamwork, teamwork interest and teamwork self-efficacy of 582 online and face-to-face students who attend the same academic program were compared. Findings: The results suggest that online students have less positive attitudes towards teamwork compared to face-to-face students although online students have a higher level of teamwork self-efficacy. Therefore, online students' relative less positive attitudes toward teamwork cannot be explained by the lack of engagement, teamwork skills or interest. Research limitations/implications: The homogeneity of the sample population is one of the limitations of the paper although it provides the opportunity for a comparative study of online and face-to-face students by controlling the majors. Practical implications: Instructors should evaluate the appropriateness of team assignments while incorporating teamwork in online classes. Originality/value: Concerns about online teamwork are discussed but have not been rigorously investigated in the literature. The authors conducted a comprehensive study involving 582 undergraduate students. The findings of this paper suggest that new approaches are needed to incorporate teamwork in online classes. The results also show that importance of building teamwork self-efficacy.